Mycobacterium avium subspecies paratuberculosis seroconversion in dairy cattle and its association with raised somatic cell count. (28th September 2019) - Barber, Benjamin M; Bell, Nick; Van Winden, Steven
Abstract : This retrospective case–control study investigates the relationship between seroconversion to Mycobacterium avium subspecies paratuberculosis (MAP) and raised somatic cell count (SCC). The study consists of 112 case cows from three dairy farms in the UK; for each case cow with a positive antibody titre, there was a seronegative control cow for comparison. Seroconversion was monitored using milk ELISA antibody titres for MAP taken at quarterly intervals. SCCs were recorded at the time a positive antibody titre was first recorded as well as at the previous and subsequent milk recording in order to explore a temporal relationship between the two events. The previous and subsequent milk recordings were a month before and after seroconversion was identified. The results showed that cows that were infected with MAP had an increased SCC around the time that they first became seropositive, providing evidence for a temporal relationship between the two events; high SCCs were particularly prevalent before and at the time of first detecting seroconversion. The explanation is being discussed that potentially an underlying, currently not studied, factor may be predisposing both events, the progression of paratuberculosis is predisposing the host to mastitis, or indeed intramammary infections help initiate paratuberculosis progression.